27+3x=4(-x+3)-27

Simple and best practice solution for 27+3x=4(-x+3)-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27+3x=4(-x+3)-27 equation:


Simplifying
27 + 3x = 4(-1x + 3) + -27

Reorder the terms:
27 + 3x = 4(3 + -1x) + -27
27 + 3x = (3 * 4 + -1x * 4) + -27
27 + 3x = (12 + -4x) + -27

Reorder the terms:
27 + 3x = 12 + -27 + -4x

Combine like terms: 12 + -27 = -15
27 + 3x = -15 + -4x

Solving
27 + 3x = -15 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
27 + 3x + 4x = -15 + -4x + 4x

Combine like terms: 3x + 4x = 7x
27 + 7x = -15 + -4x + 4x

Combine like terms: -4x + 4x = 0
27 + 7x = -15 + 0
27 + 7x = -15

Add '-27' to each side of the equation.
27 + -27 + 7x = -15 + -27

Combine like terms: 27 + -27 = 0
0 + 7x = -15 + -27
7x = -15 + -27

Combine like terms: -15 + -27 = -42
7x = -42

Divide each side by '7'.
x = -6

Simplifying
x = -6

See similar equations:

| 10+r=3r+18 | | 5(2a-4)=(2a+4) | | =c/ | | 36x(36x)=173 | | 16+3.50h=11+4.75h | | -4(x+1)=24 | | 8k^2=-48k | | 1.5x-2=x+17 | | 2y+6-4y=-10 | | n+93=-277 | | 4(3y+6)=6(2y+4) | | 3/5g-4=9 | | 18y-18=-72 | | 7/2=4x | | 2.5d+7.75=1+3.25d | | 64/(2x4) | | 7x+5-2x-3=5x+4-x+2 | | u=0x+1 | | -7z-8+3z=3 | | 245y(245y)-180=0 | | 2(9+3)=4n-2 | | 0.75s-1.75=0.625+0.75 | | 3x/4-2=a | | 8=6-2y | | -6y-11=2y+21 | | x+8+x=22 | | -949-k=-1179 | | -16b-16+17b-1=0 | | 369=11(q+19) | | 6c-7=71 | | 12-3y=6y-6 | | 5x-9y=z |

Equations solver categories